Installation of gas piping system in residential area / Mohamad Izhar Ishak and Mohd Ghazali Hariri - Ishak, Mohamad Izhar; Hariri, Mohd. Ghazali (2003)
Most houses in Malaysia are using the cylindered gas storage to get the gas supply for home use. And they don’t aware that there is a new gas supply system that doesn't need the storage tank. The gas will be distributed to houses in Malaysia using a pipe linked from the main pipe underground towards the houses. So, the main objectives for us to pick the topic as our final project are listed below: 1. To introduce to the consumer especially the residential area to the new type of gas supply system. 2. To learn the system it self. 3. To suggest the use of this system in the residential area by showing some example of piping inside a house in Taman Sri Wang in Kangar with relevant sketches and calculations. 4. To inform the reader about the advantages of using this type of gas supply system compared to the existing system. So, by going through this module, we hope that the reader will understand the system and will get enough information about the advantages of it and hopefully, it will attract more people to apply this system in their house.